Herlina Ahmad Application of Teaching Model of Developing Metacognitive Ability (DMA) In Teaching Mathematics - Ahmad, Herlina (Mathematics Department, 2017)
This research is quasi experiment research which aim to know the influence application of teaching model of developing metacognitive ability (DMA) in teaching mathematics. The subject of the research is the second year students of SMK Mega Link at computer networking department year 2016/2017. The data is taken by using research instrument of the student achievement, which already made by research for experiment class. It is given treatment application of teaching model of developing metacognitive ability (DMA). The indicator of metacognitive ability understanding the material are: (1) student are able to unclear lining the important formulas from matrix material which had been learnt; (2) students are able to make a margin note about the concept and principal in the main course of matrix which had learnt; (3) students are able to make summary of material of main course of matrix which have learnt; (4) students are able to make roadmap concept of main course which have learnt. The indicator of metacognitive ability in solving problem are: (1) students could use heuristic in solving mathematics problem, (2) students are able to apply the reverse thinking strategy in solving mathematics problem, (3) students are able to apply forward thinking procedure in solving mathematics problem, (4) students are able to apply deductive thinking procedure in solving procedure. Technique of data analysis used us t-test. Descriptive analysis result shown that 20 students of first year at computer networking department get the highest score go and the lowest are 55. Average score is 72.72 with deviation standard 11.17. Result of inferential data analysis is sig.2 tailed=0,014 which mean that application of teaching model of developing metacognitive ability (DMA) is better than without apply it. Based on research, it can conclude that there is a significant influence of applying teaching model of Cleve loping metacognitive ability (DMA) in teaching mathematics.